이유기 어린이 어머니의 이유에 관한 지식 및 이유와 식이의 실태에 관한 연구 - 유혜종 (연세대학교 보건대학원, 1987)
[한글] 모유 또는 우유가 영아에게 가장 이상적으로 영양을 공급하지만, 일정한 시기가 지나면 모유나 우유만으로는 성장발달과 건강유지에 필요한 영양을 충족시킬수 없게되어 생후 3 ∼ 4개월 이전에 이유보충식을 섭취시켜야 한다. 그러나 아직도 우리나라에서는 많은 어린이의 이유시작이 지연되고 있으며, 적절한 이유식이가 공급되지 못하고 있다. 이것은 자녀양육을 책임지고 있는 어머니들의 영양과 이유에 대한 지식이 부족하거나, 그 필요성에 대한 관심의 부족에 원인이 있다고 하겠다. 특히 이런 현상은 생활수준이나 교육수준이 낮은 계층에서 두드러지게 나타나고 있다 (문영임, 1974 ; 최진영, 1980). 이에 본인은 비교적 사회경제수준이 낮은 지역을 연구지역으로 선정하여 그 지역의 보건소 영유아실에 예방접종을 하기 위해 내소한 생후 6개월에서부터 18개월까지의 어린이를 가진 어머니 50명을 대상으로 그들의 영양과 이유에 관한 지식의 정도와 어린이에게 실시한 이유 및 식이시행 실태를 알아보고, 어머니들의 영양과 이유에 관한 지식과 이유 및 식이시행 실태와의 관계에 대하여 연구하였다. 연구방법은 면접법을 사용하였으며, 자료수집은 1987년 3월 12일부터 3월 19일 까지 면접자 2명에 의해 실시되었고, 수집된 자료는 SPSS (Statistical Package for the Social Science)를 이 용하여 전산처리 하였다. 연구와 결과는 다음과 같다. 1. 어머니들의 영양과 이유에 관한 지식은 20점이 최대가능점수였으며 평균은 11. 76이었다. 그리고 어머니의 학력이 높을수록 지식의 점수가 높았으며, 이는 통계학적으로 유의하였다(F=4.54, P<.05) 2. 영양에 대한 지식중에서 철분에 대한 지식이 가장 부족하였고, 칼슘을 제외한 탄수화물, 단백질, 지방, 비타민의 기능에 대하여 다수가 올바르게 알고 있지 못하였다. 3. 어머니들이 이상적으로 생각하는 이유의 시작시기는 평균 4.7개월이었으며, 이상적인 이유 완료시기는 평균 11.2개월이었다. 그리고 처음으로 어린이에게 먹일수 있다고 생각한 이유식으로는 유동식이라고 응답한 율이 전체의 76.0 %였다. 4. 어머니들이 어린이에게 실시한 이유 시작시기는 2개월에서부터 12개월 사이였으며, 52.0%가 유동식으로 이유를 시작했으며 이유를 완료한 17명의 어린이중 16명이 12개월이전에 이유를 완료했다고 응답했다. 5. 이유초기 (5개월이전)에는 과일즙·쥬스를 가장 많이 먹이고 있었고, 이유중기와 후기 (6개월이후)에는 밥을 가장 많이 먹이고 있었다. 6. 어머니들의 영양과 이유에 관한 지식과 이유 및 식이시행 실태와는 통계학적으로 유의한 차이가 없었다. [영문] Human milkL or cow's milk is the most desirable and complete diet for the infant, but by a certain period breast milk or cow's milk, only, does not provide sufficient amounts of certain nutrients for adequate growth and development and for maintenance of child health. Infants should, in general, be started on weaning diets before the age of three to four months. In Korea, however, the onset of weaning for many children is delayed and a proper weaning diet is not given. This is because mothers, who are responsicle for children raising, lack adequate knowledge of weaning. This can be easily seen in the children of families in the lower level of the economic status and those with minimum education. Amusing the above points, mothers from comparatively socially and economically low region in Seoul were chosen as the subjects of this study. The study attemped to find out the extent of the mothers' knowledge of nutrition and weaning, as well as what weaning and food practice were. The relationship between the mothers' knowledge of nutrition and weaning and the actual weaning and food practices is explored. The subjects of study were 50 mothers who brought their children, ages 6 to 18 months, to a Health Center for vaccination. An interview technique was used as the data gathering method. Data collection was carried out during the period from March 12, 1987 to March 19, 1987 by two interviewers and data analysts was done using the SPSS(Statistical Package for the Social Science) computrer program. The result of this study were as follows; (1) The mean score for knowledge of nutrition and weaning for the mothers was 11.76 with the highest score belong 20 points. It was found that the higher the level of the mother's education, the better the score for the knowledge. This was statistically significant. (F=4.54, p<.05). (2) Of mother's knowledge of nutrition, the most frequently missed item was the one on iron content. It was found that the mothers did not have sufficient knowledge on the function of the major nutrients; carbohydrates, protein, fat and vitamins. (3) The ideal times for strting and finishing weaning identified by the mothers were 4.7 and 11.2 months respectively. Among 50 mothers 76.0% responded that, ideally, weaning of the child should begin with a liquid diet. (4) The actual starting time of weaning ranged from 2 months of age to 12 months of age and 52.0% of children were actually started with a li quid diet. Of 17 children who were completely weaned 16 children (94.1%) had been weaned before 12 months of age. (5) In the early stage of weaning (up to 5 months) the most frequently given food was fruit juice but in the middle and the later stages (from 6 mouths) boiled rice was most frequently given. (6) They were no statistically significant relationships between mother's knowledge of nutrition and weaning and their actual weaning and food practice.
보건학과/석사